Central Bank Emergency Support to Securities Markets - King, Darryl (IMF Working Papers; Working Paper ;, 2017)
This paper considers the central bank mandate with respect to financial stability and identifies the links to the functioning of securities markets. It argues that while emergency support to securities markets is an important part of the crisis management response, a high bar should be set for its use. Importantly, it should be used only as part of a comprehensive policy package. The paper considers what types of securities markets may be important for financial stability, what market conditions could trigger emergency support measures, and how programs can be designed to restore market functioning while minimizing moral hazard.